Microparticles in cardiovascular diseases - VanWijk, Marja J; VanBavel, E; Sturk, A; Nieuwland, R (Cardiovascular research, 2003)
Microparticles are membrane vesicles released from many different cell types. There are two mechanisms that can result in their formation, cell activation and apoptosis. In these two mechanisms, different pathways are involved in microparticle generation. Microparticle generation seems to be a well regulated process. Microparticles vary in size, phospholipid and protein composition. They have a potent pro-inflammatory effect, promote coagulation and affect vascular function. Since these processes are all involved in the pathogenesis of cardiovascular disease and circulating microparticle numbers are altered in many cardiovascular diseases, a role for microparticles in the pathogenesis of cardiovascular diseases is likely. Although hard evidence for a role of microparticles in cardiovascular diseases at present is still only limited, new evidence is accumulating rapidly to support this theory. Elucidation of the microparticle composition and the mechanisms involved in exertion of their effects will supply this evidence and enable us to develop additional intervention strategies for prevention and treatment of cardiovascular diseases.